Analisis Technology Readiness Index (Tri) Terhadap Penerapan Mekanisasi Intensif Pada Kegiatan Onfarm Di Lingkup Palmco - Zulkifli Zein; Bahrul Ulum; Azhari Rizal; Adi Rimbawanto; Oni Apriyanto (Universitas Tidar, 2026)
The transformation of the oil palm industry toward more efficient production systems has accelerated the implementation of mechanization in plantation operations. The success of mechanization adoption is determined not only by the availability of technology but also by the readiness of human resources to accept and utilize such technology. This study aims to analyze the level of technology readiness for intensive mechanization implementation in on-farm operations within PT Perkebunan Nusantara IV (PalmCo). A quantitative descriptive approach was employed using the Technology Readiness Index (TRI), which consists of four dimensions: optimism, innovativeness, discomfort, and insecurity. Data were collected through questionnaires distributed to respondents from six PalmCo estates representing Regions I, II, and III. The study covered mechanization in land preparation and planting, fertilization, maintenance and weed control, harvesting, and transportation activities. Data were analyzed by calculating the technology readiness index and classifying the results into low, medium, and high technology readiness categories. The results showed that mechanization in land preparation and fertilization achieved TRI values of 3.437 and 2.966, respectively, indicating Medium Technology Readiness. In contrast, weed control and harvesting-transportation activities recorded TRI values of 2.866 and 2.804, respectively, indicating Low Technology Readiness. Optimism was identified as the most influential dimension contributing to technology readiness across all mechanization activities. The lower readiness levels were mainly associated with plantation topography, limited supporting infrastructure, and the absence of fully integrated mechanization implementation. These findings provide valuable insights for PalmCo in developing more effective mechanization strategies tailored to the operational characteristics of oil palm plantations.